High‐Throughput Sequencing in Aquaculture Disease Investigations: Challenges and Opportunities for Implementation - Francisca Samsing; Phoebe Arbon; Matthew Arnold; Andrew C. Barnes; David Bass; Joy A. Becker; Jerusha Bennett; Charles Caraguel; Jeremy Carson; Vincenzo A. Costa; Thomas Dumond; Jemma Geoghegan; et al. (Reviews in Aquaculture, 2026)
The current generation of sequencing technologies can produce terabases of data with exceptional accuracy and speed, at a fraction of the cost of older methods. Despite this unprecedented power, adoption into aquaculture health management presents several challenges, including identifying where such capability may be optimally deployed. Here we synthesise discussions from a structured expert workshop held at the 2025 Aotearoa Aquatic Diseases Symposium in Dunedin, New Zealand, where experts from industry, government and academia explored the challenges and opportunities for adopting high‐throughput sequencing (HTS) to support disease investigations in aquaculture. Workshop participants identified key applications for HTS, including pathogen discovery during unexplained mortality events and source attribution in epidemics, but also noted technical, regulatory and social challenges for widespread adoption. These include the need for standardised sampling and bioinformatic workflows, data sovereignty, equitable access to the technology and uncertainty around interpreting detection of notifiable pathogens. Targeted research and coordinated regulatory frameworks will be essential to guide responsible use of HTS and determine where it adds value relative to existing approaches. Clarifying these opportunities and constraints will guide the responsible adoption of HTS into aquaculture health management to support sustainable growth for the sector.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

A revised Proterozoic tectono-stratigraphy of the South Nicholson region, Northern Territory, Australia—insights from SHRIMP U–Pb detrital zircon geochronology - C. J. Carson; N. Kositcin; J. R. Anderson; P. A. Henson (Australian Journal of Earth Sciences, 2026)

Shale brittleness within the Paleoproterozoic Isa Superbasin succession in the South Nicholson region, Northern Australia - A. H. E. Bailey; A. J. M. Jarrett; L. Wang; B. L. Reno; E. Tenthorey; C. Carson; P. Henson (Australian Journal of Earth Sciences, 2026)

Belowground performance of novel short-stature maize under varying nitrogen rates across contrasting soil types - Binod Joshi; Raziel A. Ordóñez; Daniel Quinn; Chad Penn; Carson Pearl; Tony J. Vyn; Yichao Rui (Field Crops Research, 2026)

Lag in Effective Population Size Decline Amid Demographic Collapse: A Case Study of the Delta Smelt ( Hypomesus transpacificus ) - Amanda J. Finger; Melanie E. F. LaCava; Evan W. Carson; James A. Hobbs; Tien‐Chieh Hung; Matthew L. Nobriga; Leo Polansky; Robin S. Waples (Molecular Ecology, 2026)
Effective population size ( N e ), census size ( N c ) and their ratio ( N e / N c ) are widely used indicators in conservation genetics, yet long‐term empirical data tracking of all three metrics over long time scales in wild populations remains rare. Using monitoring data from 1995 to 2020, we examined temporal dynamics of N e , N c and their relationship during the demographic collapse of Delta Smelt ( Hypomesus transpacificus ), an endangered fish endemic to the San Francisco Estuary, California, USA. We estimated N e for 21 annual cohorts using restriction site‐associated DNA sequencing data, applying the linkage disequilibrium method, temporal method and a recently developed combined method. Abundance was represented by model‐based survey indices ( N c *). N e varied substantially through time (145–1928), declining in recent years but remaining above commonly cited conservation thresholds for long‐term persistence (e.g., N e > 500) until the final years of collapse. N e was positively correlated with N c * ( r = 0.58), but the shallow slope (β = 0.25) indicates that demographic decline outpaced genetic decline. N e / N c * was consistently low (0.0001–0.056), but it increased significantly through time. Our results show that genetic erosion may lag behind demographic collapse and that N e / N c * is not constant and therefore cannot be easily inferred from either variable alone. This study demonstrates the need for additional empirical data sets to facilitate interpretation of N e , N c * and N e / N c * for the conservation of global biodiversity.

Population genetic and phylogenetic analysis of pupfish (Cyprinodon, Cyprinodontidae) in the Rio Conchos and adjacent rivers reveals hidden diversity - Casey Ernest; Michael Tobler; Ma. Lourdes De Lozano-Vilano; Mauricio De La Maza-Benignos; Tracy A. Diver; Wade D. Wilson; Thomas F. Turner; Evan W. Carson (Conservation Genetics, 2026)

Profiles of polysubstance exposure in youth with fetal alcohol spectrum disorders and the association with neurodevelopmental outcomes - Madeline N. Delage; Emily L. Speybroeck; Alesia A. Richardson; Lynn L. Cole; Carson Kautz-Turnbull; Christie L.M. Petrenko (Neurotoxicology and Teratology, 2026)

Incorporating corrosion design constraints in desalination process optimization: A case study in mechanical vapor compression - Carson I. Tucker; Oluwamayowa O. Amusat; Adam A. Atia; Alexander V. Dudchenko; Timothy V. Bartholomew; Meagan S. Mauter (Desalination, 2026)

Ecology and Reproduction of Bunodeopsis in Tropical Northwestern Atlantic Seagrass Ecosystems - Isabel A. M. Pen; Luisa F. Dueñas; Juan Armando Sánchez; Diana Carolina Vergara‐Flórez; Carlos E. Gómez; Vladimir Tovar‐Bolaños; Juan Andrés Palacios; Jorge A. Moreno; Marina I. Stoilova; Carly Lo; Carson Kephart; Amber Fredenburg; et al. (Marine Ecology, 2026)
The seagrass ecosystems of the Tropical Northwestern Atlantic (TNA) host three described species of sea anemones in the genus Bunodeopsis Andres, 1881 (Enthemonae: Metridioidea: Acuticulata): B. antilliensis , B. globulifera , and B. pelagica . Due to their small size and nocturnal nature, many aspects of their basic biology and distribution remain unknown. To investigate their ecology and distribution, we surveyed five TNA ecoregions: Greater Antilles (Puerto Rico), Southern Caribbean (Curaçao), Southwestern Caribbean (Colombia and Panama), Western Caribbean (Belize and Mexico), and the Southern Gulf of Mexico (Mexico). Specimens were identified to genus, documented in situ and captively maintained for behavioral observations. Field methods combined nighttime snorkel observations and collection with macro and timelapse photography to document behavior, morphology, and asexual reproduction. We observed extensive morphological variation and presumably clonal aggregations in situ. Captive observations corroborated previously reported modes of asexual reproduction including pedal and vesicular scission, as well as revealed the previously unreported mode of transverse fission. Field observations revealed novel ecological interactions including predation on amphinomid polychaetes, association with the sacoglossan Elysia crispata , and predation by a reptantian ribbonworm (Nemertea: Reptantia). In Belize, standardized diurnal and nocturnal quadrat surveys at fixed distances from shore quantified Bunodeopsis spp. detectability, which was significantly greater at night regardless of observation depth. Nighttime detectability was approximately three times higher than during the day, supporting the conclusion that the lack of an abundance of reports of Bunodeopsis spp. is likely an artifact of underdetection than true rarity. The new occurrences reported here more than double previous records on GBIF, contributing resolution to the distribution of Bunodeopsis spp. Across five ecoregions in the TNA. These findings underscore the ecological importance of this genus of sea anemones in seagrass ecosystems and emphasize the need for surveys that target small, nocturnal, and understudied marine invertebrates.

Impacts of hybrid selection and nitrogen fertilization on root-derived carbon inputs in maize - Carson Pearl; Raziel A. Ordóñez; Cindy Prescott; Daniel Quinn; Roland Wilhelm; Chad Penn; Binod Joshi; Yichao Rui (Plant and Soil, 2026)
Background and Aims Root-derived carbon (C) inputs are increasingly recognized as important precursors to soil organic carbon (SOC). However, the extent to which these inputs can be influenced by nitrogen (N) fertilizer management and plant stature remains poorly understood. This study investigated how N fertilization rate and maize hybrid stature trade off between above- and belowground performance, including investment in root traits, exudation, and soil microbial C pools. Methods Tall- and short-stature maize (Zea mays) hybrids, from Bayer’s breeding pipeline, were grown in a pot experiment in two soil matrices (sandy and loamy), with N fertilization rates of 0, 90, 180, and 270 kg N ha⁻ 1 . C pools in above- and belowground compartments were assessed, including root exudates, root biomass and length, soil microbial biomass C, and total soil C. Results Soil matrix and maize hybrids of different stature primarily explained differences in root exudation and belowground C inputs. Short-stature maize produced 22% greater dry root biomass than tall maize across N treatments. Loamy soils accumulated higher soil microbial biomass C and peaked at intermediate N rates, where fertilization achieved the greatest response in root biomass and C inputs. The highest N rates resulted in lower belowground C investment (particularly > 180 kg N ha⁻ 1 in loamy soil). Conclusion Maize hybrid selection and N fertilization interaction influenced root-derived C inputs and soil microbial biomass, with short-stature hybrids and moderate N rates enhancing belowground C allocation. These findings suggest that short-stature maize and avoiding excessive N fertilizer rates can enhance root contributions to key soil C pools.

Inter-method differences (SIMS vs. IRMS) in oxygen isotope fractionation: insights from Chinook salmon otoliths - Kohma Arai; Malte Willmes; George E. Whitman; Kenneth W. Zillig; Cassidy J. Cooper; Nozomi Matsuda; Elizabeth A. Bell; Kevin D. McKeegan; Levi S. Lewis; Carson A. Jeffres; Rachel C. Johnson (Geochimica et Cosmochimica Acta, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

The discovery and preclinical pharmacology of JNJ-10450232 (NTM-006), a centrally penetrant, non-opioid structural analog of acetaminophen with comparable analgesic and anti-pyretic properties but no evidence of hepatotoxicity - Christopher M. Flores; John R. Carson; Ellen E. Codd; Scott L. Dax; Edwin K. Kuffner; Paul L. Stahle; Robert A. Neff; Gary E. Eichenbaum (Regulatory Toxicology and Pharmacology, 2025)

Evaluation of SARS-CoV-2 antibody detection methods for wild Cervidae - Joshua Hewitt; Grete Wilson-Henjum; Jeffrey C. Chandler; Aaron T. Phillips; Diego G. Diel; W. David Walter; Alec Baker; Jennifer Høy-Petersen; Guillaume Bastille-Rousseau; Tadao Kishimoto; George Wittemyer; Jeremy Alder; et al. (Preventive Veterinary Medicine, 2025)

Associations of volatile organic compounds with accelerated epigenetic aging in the lungs of smokers and electronic cigarette users - Ajmal Khan; Carson Richardson; Joseph P. McElroy; Amarnath Singh; Daniel Y. Weng; Sahar Kamel; Sarah A. Reisinger; Mark D. Wewers; Peter G. Shields; Min-Ae Song (Science of The Total Environment, 2025)

Impact of sarcopenia and obesity on skeletal muscle size, gene expression, and mitochondrial function - Hector G. Paez; Christopher R. Pitzer; Jessica L. Halle; Peter J. Ferrandi; James A. Carson; Junaith S. Mohamed; Stephen E. Alway (GeroScience, 2025)
Skeletal muscle is a primary tissue of dysfunction during both aging and obesity. Recently, the coincidence of obesity and aging has gained attention due to the intersection of the obesity epidemic with an aging demographic. Both aging and obesity are associated with marked defects in skeletal muscle metabolic health. Despite these findings, we have a poor understanding of how obesity and aging may interact to impact skeletal muscle mass and metabolic health. Therefore, we investigated the impact of high-fat diet (HFD)-induced obesity on skeletal muscle mass, mitochondrial function, transcriptomics, and whole-body metabolism in young and aged mice. We observed main effects of diet and age on several measures of whole-body metabolic function (VO 2 , VCO 2 , and RER). Complex I-driven mitochondrial proton leak was significantly elevated by HFD-induced obesity across both age groups; however, a main effect of aging for reduced complex I leak was detected in the soleus muscle. Interestingly, aged animals fed a HFD did not exhibit lower muscle mass than chow-fed young animals, but did present with stark increases in muscle triglyceride content and a unique transcriptional response to HFD. HFD-induced obesity impacted the muscle transcriptome differently in the muscles of young and aged mice, indicating that obesity can change altered gene expression with age. Our findings suggest that the presence of obesity can both compound and counteract age-associated changes to muscle mass, gene expression, and mitochondrial function.

Impact of climate change on the nitrogen budget of a dairy farm in the Fraser Valley, British Columbia, Canada - Sarah J. Pogue; Marcos R.C. Cordeiro; Alan Rotz; Carson Li; Roland Kröbel; Karen A. Beauchemin; Derek Hunt; Shabtai Bittman (Agricultural Systems, 2025)

Diet Driven Differences in Host Tolerance Are Linked to Shifts in Global Gene Expression in a Common Avian Host‐Pathogen System - Erin L. Sauer; Carson Stacy; Weston Perrine; Ashley C. Love; Jeffrey A. Lewis; Sarah E. DuRant (Molecular Ecology, 2025)
Wildlife have become increasingly dependent on anthropogenic resources, altering interactions between individuals and subsequently disease transmission. Further, nutritional quantity and quality impact an individual's ability to mitigate damage caused by infectious disease. Thus, understanding how diet affects immune function is critical for predicting disease severity and transmission. Here, we use transcriptomics to explore the previously unstudied molecular mechanisms underpinning diet‐driven differences in pathogen tolerance. Using a widespread avian bacterial pathogen, we find significant diet‐driven differences in the expression of many genes encoding immune response and translational machinery proteins. Prior to infection, protein‐fed birds are more transcriptionally primed for infection than lipid‐fed birds, resulting in greater tolerance for protein‐fed birds during the recovery period. Given the importance of human supplemented food in wildlife disease systems, the molecular mechanisms by which interactions between diet and infection emerge provide insight into the ecological and immunological consequences of human behaviour on wildlife disease.

A global survey for dust devil vortices on mars using MRO context camera images enabled by neural networks - Susan J. Conway; Valentin T. Bickel; Lori K. Fenton; Manish R. Patel; Helen C. Carson; Antoine Blouin; Justin Crevier; Evan Blanc; Bao Nhi Nguyen; James A. Holmes; Brian Jackson; Lonneke Roelofs (Planetary and Space Science, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Electronic cigarettes alter cardiac rhythm and heart rate variability hyperacutely in mice - Jocelyn A. Castellanos; Carson G. Cornett; David H. Gonzalez; Liqiao Li; Karla Luna; Holly R. Middlekauff; Rajat Gupta; Maria C. Jordan; Dennis Rünger; Yifang Zhu; Xuesi M. Shao; Kenneth P. Roos; et al. (Toxicology and Applied Pharmacology, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Optimising Outbreak Investigation, Surveillance and Discovery of Pathogens in Aquaculture Using Unbiased Metatranscriptomics - Vincenzo A. Costa; Richard J. Whittington; Charles Caraguel; Joy A. Becker; Kerrie E. Wiley; Christine Huynh; Jeremy Carson; Francisca Samsing (Reviews in Aquaculture, 2025)
Emerging infectious diseases are a major threat to global aquaculture production and are projected to increase in frequency due to anthropogenic stressors and climate change. Our ability to screen the global aquatic ‘infectome’ is dramatically improving through unbiased metatranscriptomic (i.e., total RNA) sequencing. Despite recent advances in molecular diagnostics and next‐generation sequencing, outbreak investigation in aquaculture often encounters limitations due to the targeted nature of conventional techniques, which may only capture a small portion of the diverse array of disease‐causing agents present in nature, sometimes requiring years to resolve. Here, we propose that unbiased metatranscriptomic sequencing serves as a cost‐effective and powerful technique for characterising pathogens during disease outbreaks and in surveillance programmes. In doing so, we offer a diagnostic framework to mitigate infectious disease threats to global aquaculture. We emphasise the importance of combining rapid metatranscriptomics with traditional techniques for a holistic examination of the causes of unknown aetiologies in aquatic animals, and how it can be used to examine host responses in parallel with pathogen discovery. We suggest that the integration of metatranscriptomics into aquaculture will require upskilling, proficiency testing, user‐friendly bioinformatic tools and open data sharing. Furthermore, it is essential to establish a reporting framework—with analytical guidelines—that ensures the protection of animal industries while safeguarding trade interests.

Turbidity and temperature effects on growth and gene transcription of threatened juvenile Longfin Smelt (Spirinchus thaleichthys) - Felix Biefel; Christina Pasparakis; Dennis E. Cocherell; Tien-Chieh Hung; Evan W. Carson; Nann A. Fangue; Juergen P. Geist; Anne E. Todgham; Richard E. Connon (Aquaculture, 2024)

Bayesian statistical analysis reveals spatial heterogeneity in Cyclone Thane deposits from Southeast India - C. Gouramanis; A. Karthik; S. Srinivasalu; S. Carson; A.D. Switzer (Marine Geology, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Internal sand bank seismic stratigraphy provides insight into paleo-barrier island preservation - Carson B. Miller; John A. Goff; Sean P.S. Gulick; Davin J. Wallace; Christopher M. Lowery (Marine Geology, 2024)

Understanding and valuing human connections to deep-sea methane seeps off Costa Rica - Olívia S. Pereira; Mark Jacobsen; Richard Carson; Jorge Cortés; Lisa A. Levin (Ecological Economics, 2024)

Native tree species prosper while exotics falter during gap-phase regeneration, but only where deer densities are near historical levels - Anthony C. Yacucci; Walter P. Carson; Jenna C. Martineau; Curtis D. Burns; Brian P. Riley; Alejandro A. Royo; Thomas P. Diggins; Ian J. Renne (New Forests, 2024)

Evaluation of registration-based vs. manual segmentation of rhesus macaque brain MRIs - Joey A. Charbonneau; Brittany Davis; Erika P. Raven; Bhakti Patwardhan; Carson Grebosky; Lucas Halteh; Jeffrey L. Bennett; Eliza Bliss-Moreau (Brain Structure and Function, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Biophysical effects of an old tundra fire in the Brooks Range Foothills of Northern Alaska, U.S.A - Eric A. Miller; Carson A. Baughman; Benjamin M. Jones; Randi R. Jandt (Polar Science, 2024)

Product-inhibition feedbacks, not microbial population level tradeoffs or soil pH, regulate decomposition potential under nutrient eutrophication - Matthew A. Nieland; Christine M. Carson; Victoria Floyd; Lydia H. Zeglin (Soil Biology and Biochemistry, 2024)

Global Patterns of Metal and Other Element Enrichment in Bog and Fen Peatlands - Chetwynd Osborne; Spencer Gilbert-Parkes; Graeme Spiers; Louis James Lamit; Erik A. Lilleskov; Nathan Basiliko; Shaun Watmough; Roxanne Andersen; Rebekka E. Artz; Brian W. Benscoter; Luca Bragazza; Suzanna L. Bräuer; et al. (Archives of Environmental Contamination and Toxicology, 2024)

Phylogenetic relationships and introduction history inferred from complete mitochondrial genomes of four smelts (Osmeridae) of the modern San Francisco Estuary - Marzieh Asadi Aghbolaghi; Aaron P. Maloy; Jason A. Coombs; Tien-Chieh Hung; Evan W. Carson (Zoologischer Anzeiger, 2024)

Saturated Fat Intake and the Prevention and Management of Cardiovascular Disease in Adults: An Academy of Nutrition and Dietetics Evidence-Based Nutrition Practice Guideline - Sarah A. Johnson; Carol F. Kirkpatrick; Nicole H. Miller; Jo Ann S. Carson; Deepa Handu; Lisa Moloney (Journal of the Academy of Nutrition and Dietetics, 2023)

Associations between PM2.5 and O3 exposures and new onset type 2 diabetes in regional and national samples in the United States - Tara P. McAlexander; Victoria Ryan; Jalal Uddin; Rania Kanchi; Lorna Thorpe; Brian S. Schwartz; April Carson; Deborah B. Rolka; Samrachana Adhikari; Jonathan Pollak; Priscilla Lopez; Megan Smith; et al. (Environmental Research, 2023)

Understory plant growth forms respond independently to combined natural and anthropogenic disturbances - Michelle Elise Spicer; Alejandro A. Royo; John W. Wenzel; Walter P. Carson (Forest Ecology and Management, 2023)

Changing litter composition following the dual invasion of Amur honeysuckle and the emerald ash borer alters fungal driven decomposition in Midwestern forests - Adam M. Reed; Carson Richardson; Megan A. Rúa (Biological Invasions, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Does fine‐scale habitat diversity promote meaningful phenotypic diversity within a watershed network? - Robert A. Lusardi; Randy Dahlgren; Erwin Van Nieuwenhuyse; George Whitman; Carson Jeffres; Rachel Johnson (Ecology, 2023)

First record of plastic ingestion by a freshwater stingray - Paulo A.A. Trindade; Lúcio D.M. Brabo; Ryan Andrades; Valter M. Azevedo-Santos; Marcelo C. Andrade; Laura Candore; Serena B. Cabigliera; David Chelazzi; Alessandra Cincinelli; Carson A. Jeffres; Tommaso Giarrizzo (Science of The Total Environment, 2023)

Cold temperature stress and damaged skin induced high mortality in barramundi ( Lates calcarifer ) challenged with Vibrio harveyi - Francisca Samsing; William Zhang; Ruth N. Zadoks; Richard Whittington; Carola Venturini; Carla Giles; Jeremy Carson; Joy A. Becker (Journal of Fish Diseases, 2023)
Most diseases in aquaculture are caused by opportunistic pathogens. One of them, Vibrio harveyi , is a widespread Gram‐negative bacterium that has become an important pathogen of aquatic species in marine environments. Here, we propose the use of the causal pie model as a framework to conceptualize the causation of vibriosis in juvenile barramundi ( Lates calcarifer ) and to establish an effective challenge model. In the model, a sufficient cause, or the causal pie, is a constellation of component causes that lead to an outcome (e.g. vibriosis). In the pilot study, a high cumulative mortality (63.3% ± 10.0%, mean ± SE) was observed when V. harveyi was administered by intraperitoneal injection using a high challenge dose [10 7 colony‐forming units (CFU) fish −1 ], but low or no mortality was observed in fish subject to cold stress or fish with intact skin when challenged by immersion. We, therefore, tested the use of a skin lesion (induced with a 4‐mm biopsy punch) combined with cold temperature stress to induce vibriosis following the causal pie model. After challenge, fish were immediately subject to cold stress (22°C) or placed at an optimal temperature of 30°C. All groups were challenged with 10 8 CFU mL −1 for 60 min. A considerably higher mortality level (72.7% ± 13.9%) was observed in fish challenged with both a skin lesion and cold stress compared with mortality in fish only having a skin lesion (14.6% ± 2.8%). V. harveyi was re‐isolated from all moribund fish and was detected by species‐specific real‐time PCR in gills, head kidney and liver, regardless of challenge treatment confirming vibriosis as the cause of disease. Parenchymal tissues had histopathological changes consistent with vibriosis. Whole‐genome sequence (WGS) is provided for the Vibrio harveyi isolate examined in this study. Overall, the causal pie model was a useful framework to conceptualize the design of the experimental challenge model, in which both cold stress and skin damage were identified as component causes of vibriosis with high mortality. This conceptual framework can be applied to other opportunistic pathogens in aquaculture or to the study of co‐infections in fish.

Acardius acephalus in an aborted lamb - A. Morey Matamalas; F. Ridout; J. Dubuc; C. Bianco; R. Reichel; A. Carson (Journal of Comparative Pathology, 2023)

Associations between demographic and parental factors and infant sleep characteristics - Zhiguang Zhang; Brittany A. Matenchuk; Rachel J. Skow; Margie H. Davenport; Valerie Carson (Sleep and Biological Rhythms, 2023)

Multiple and contrasting pressures determine intraspecific phytochemical variation in a tropical shrub - Andrea E. Glassmire; Walter P. Carson; Angela M. Smilanich; Lora A. Richards; Christopher S. Jeffrey; Craig D. Dodson; Casey S. Philbin; Garcia L. Humberto; Lee A. Dyer (Oecologia, 2023)

The resting serum metabolome in response to short-term sprint interval training - Ian A. J. Darragh; Tom P. Aird; Aifric O’Sullivan; Brendan Egan; Brian P. Carson (European Journal of Applied Physiology, 2023)

Serotonin transporter availability in physically aggressive personality disordered patients: associations with trait and state aggression, and response to fluoxetine - Daniel R. Rosell; Mark Slifstein; Judy Thompson; Xiaoyan Xu; M. Mercedes Perez-Rodriguez; Margaret M. McClure; Erin A. Hazlett; Antonia S. New; Nabeel Nabulsi; Yiyun Huang; Richard E. Carson; Larry S. Siever; et al. (Psychopharmacology, 2023)

Multiple trophic pathways support fish on floodplains of California's Central Valley - Bobby J. Nakamoto; Carson A. Jeffres; Nicholas J. Corline; Mollie Ogaz; Christina J. Bradley; Joshua H. Viers; Marilyn L. Fogel (Journal of Fish Biology, 2023)
We used compound‐specific isotope analysis of carbon isotopes in amino acids (AAs) to determine the biosynthetic source of AAs in fish from major tributaries to California's Sacramento‐San Joaquin river delta ( i . e ., the Sacramento, Cosumnes and Mokelumne rivers). Using samples collected in winter and spring between 2016 and 2019, we confirmed that algae are a critical component of floodplain food webs in California's Central Valley. Results from bulk stable isotope analysis of carbon and nitrogen in producers and consumers were adequate to characterize a general trophic structure and identify potential upstream and downstream migration into our study site by American shad Alosa sapidissima and rainbow trout Oncorhynchus mykiss , respectively. However, owing to overlap and variability in source isotope compositions, our bulk data were unsuitable for conventional bulk isotope mixing models. Our results from compound‐specific carbon isotope analysis of AAs clearly indicate that algae are important sources of organic matter to fish of conservation concern, such as Chinook salmon Oncorhynchus tshawytscha in California's Central Valley. However, algae were not the exclusive source of energy to metazoan food webs. We also revealed that other sources of AAs, such as bacteria, fungi and higher plants, contributed to fish as well. While consistent with the well‐supported notion that algae are critical to aquatic food webs, our results highlight the possibility that detrital subsidies might intermittently support metazoan food webs.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Obesity as a premature aging phenotype — implications for sarcopenic obesity - Emily Nunan; Carson L. Wright; Oluwayemisi A. Semola; Madhan Subramanian; Priya Balasubramanian; Pamela C. Lovern; Ibra S. Fancher; Joshua T. Butcher (GeroScience, 2022)
Obesity and aging have both seen dramatic increases in prevalence throughout society. This review seeks to highlight common pathologies that present with obesity, along with the underlying risk factors, that have remarkable similarity to what is observed in the aged. These include skeletal muscle dysfunction (loss of quantity and quality), significant increases in adiposity, systemic alterations to autonomic dysfunction, reduction in nitric oxide bioavailability, increases in oxidant stress and inflammation, dysregulation of glucose homeostasis, and mitochondrial dysfunction. This review is organized by the aforementioned indices and succinctly highlights literature that demonstrates similarities between the aged and obese phenotypes in both human and animal models. As aging is an inevitability and obesity prevalence is unlikely to significantly decrease in the near future, these two phenotypes will ultimately combine as a multidimensional syndrome (a pathology termed sarcopenic obesity). Whether the pre-mature aging indices accompanying obesity are additive or synergistic upon entering aging is not yet well defined, but the goal of this review is to illustrate the potential consequences of a double aged phenotype in sarcopenic obesity. Clinically, the modifiable risk factors could be targeted specifically in obesity to allow for increased health span in the aged and sarcopenic obese populations.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The hidden legacy of megafaunal extinction: Loss of functional diversity and resilience over the Late Quaternary at Hall’s Cave - Carson P. Hedberg; S. Kathleen Lyons; Felisa A. Smith (Global Ecology and Biogeography, 2022)
Aim Functional traits mediate the interactions of species among themselves and with their environment, providing a link between diversity and ecosystem function. Crucially, the loss of biodiversity can jeopardize the functionality of ecosystems. Much focus is on predicting the impacts of current and future species loss; however, modern ecosystems have undergone biodiversity decline throughout the Late Quaternary, starting with the Pleistocene megafaunal extinctions. Thus, the fossil record offers the opportunity to investigate the long‐term legacy of biodiversity erosion and how this is affecting modern ecosystems in a cumulative manner. We aimed to investigate changes in functional diversity and redundancy of a local mammal community at Hall’s Cave, a site with a continuous record from 21,000 years ago to the present. Additionally, we included several common introduced species in the modern community to test whether they restore some lost ecological function. Location Central Texas. Time period Late Pleistocene to Present. Major taxa studied Mammals. Methods We used eight functional traits (mass, diet, arboreality, cursoriality, soil disturbance, group size, activity period and migration habit), which, collectively, describe the ecological role of a species and its influence on ecosystem processes, to construct a multidimensional functional space. The functional richness, range and distribution of the Hall’s Cave community and the degree of functional redundancy were characterized statistically over time. Results We found that declines in functional diversity were greater than expected given the decrease in species richness, implying that lost taxa contributed higher than average distinct ecological function. Functional distances between the remaining species increased through time, leading to reduced functional redundancy in younger communities. However, recently introduced taxa increased functional diversity to levels similar to those in the Holocene and partly restored the functional space occupied by Late Pleistocene fauna. Main conclusions Our local‐scale analysis demonstrates how prolonged biodiversity erosion not only leads to functionally depauperate communities, but, crucially, lowers ecological resilience to future disturbance.

RNA sequencing of LX-2 cells treated with TGF-β1 identifies genes associated with hepatic stellate cell activation - Jack P. Carson; Mark W. Robinson; Grant A. Ramm; Geoffrey N. Gobert (Molecular Biology Reports, 2021)
Background Hepatic stellate cells (HSCs) are liver-resident myofibroblast precursors responsible for the production of collagen and maintenance of the hepatic extracellular matrix (ECM). As such, they are generally associated with fibrotic liver diseases. HSCs become “activated” in response to tissue damage or pathogen invasion, a process most commonly driven by transforming growth factor-β1 (TGF-β1). Despite this, the full extent of TGF-β1 signalling in these cells is poorly understood. Clarifying the range and diversity of this signalling will further improve our understanding of the process of HSC activation. Methods and results RNA sequencing was used to quantitate the transcriptomic changes induced in LX-2 cells, an activated human HSC line, following TGF-b1 treatment. In total, 5,258 genes were found to be significantly differentially expressed with a false discovery rate cut-off of < 0.1. The topmost deregulated of these genes included those with no currently characterised role in either HSC activation or fibrotic processes, including CIITA and SERPINB2. In silico analysis revealed the prominent signalling pathways downstream of TGF-β1 in LX-2 cells. Conclusions In this study, we describe the genes and signalling pathways significantly deregulated in LX-2 cells following TGF-β1 treatment. We identified several highly deregulated genes with no currently characterised role in HSC activation, which may represent novel mediators of fibrotic responses in HSCs or the liver macroenvironment. This work may be of use in the identification of new markers of liver fibrosis and could provide insight into prospective genes or pathways that might be targeted for the amelioration of fibrotic liver disease in the future.

Immature Male Chimpanzees’ (Pan troglodytes schweinfurthii) Social Relationships with Adult Males, but Not Peers, Persist into Adulthood - Joel Bray; Carson M. Murray; Ian C. Gilby; Margaret A. Stanton (International Journal of Primatology, 2021)

Correction to: Temporal emergence of age-associated changes in cognitive and physical function in vervets (Chlorocebus aethiops sabaeus) - Brett M. Frye; Payton M. Valure; Suzanne Craft; Mark G. Baxter; Christie Scott; Shanna Wise-Walden; David W. Bissinger; Hannah M. Register; Carson Copeland; Matthew J. Jorgensen; Jamie N. Justice; Stephen B. Kritchevsky; et al. (GeroScience, 2021)

Association Between Greater Cerebellar Network Connectivity and Improved Phonemic Fluency Performance After Exercise Training in Older Adults - Junyeon Won; Yasmeen Faroqi-Shah; Daniel D. Callow; Allison Williams; Adewale Awoyemi; Kristy A. Nielson; J. Carson Smith (The Cerebellum, 2021)

Temporal emergence of age-associated changes in cognitive and physical function in vervets (Chlorocebus aethiops sabaeus) - Brett M. Frye; Payton M. Valure; Suzanne Craft; Mark G. Baxter; Christie Scott; Shanna Wise-Walden; David W. Bissinger; Hannah M. Register; Carson Copeland; Matthew J. Jorgensen; Jamie N. Justice; Stephen B. Kritchevsky; et al. (GeroScience, 2021)

Sex differences in changes of protein synthesis with rapamycin treatment are minimized when metformin is added to rapamycin - Christopher A. Wolff; Marcus M. Lawrence; Hunter Porter; Qian Zhang; Justin J. Reid; Jaime L. Laurin; Robert V. Musci; Melissa A. Linden; Frederick F. Peelor; Jonathan D. Wren; Joseph S. Creery; Kyle J. Cutler; et al. (GeroScience, 2021)

Post-windthrow salvage logging increases seedling and understory diversity with little impact on composition immediately after logging - Jacob B. Slyder; John W. Wenzel; Alejandro A. Royo; Michelle Elise Spicer; Walter P. Carson (New Forests, 2020)

Consequences of maternal loss before and after weaning in male and female wild chimpanzees - Margaret A. Stanton; Elizabeth V. Lonsdorf; Carson M. Murray; Anne E. Pusey (Behavioral Ecology and Sociobiology, 2020)

Nitrogen Retention of Terricolous Lichens in a Northern Alberta Jack Pine Forest - Adam Bird; Shaun A. Watmough; Michael A. Carson; Nathan Basiliko; Andrew McDonough (Ecosystems, 2019)

Novel life history tactic observed in fall‐run Chinook Salmon - Carson A. Jeffres; Christopher C. Adams (Ecology, 2019)

Interlimb transfer and generalisation of learning in the context of persistent failure to accomplish a visuomotor task - D. A. E. Bolton; A. R. Buick; T. J. Carroll; R. G. Carson (Experimental Brain Research, 2019)

Correction to: Gene therapy knockdown of VEGFR2 in retinal endothelial cells to treat retinopathy - Aaron B. Simmons; Colin A. Bretz; Haibo Wang; Eric Kunz; Kassem Hajj; Carson Kennedy; Zhihong Yang; Thipparat Suwanmanee; Tal Kafri; M. Elizabeth Hartnett (Angiogenesis, 2018)

Gene therapy knockdown of VEGFR2 in retinal endothelial cells to treat retinopathy - Aaron B. Simmons; Colin A. Bretz; Haibo Wang; Eric Kunz; Kassem Hajj; Carson Kennedy; Zhihong Yang; Thipparat Suwanmanee; Tal Kafri; M. Elizabeth Hartnett (Angiogenesis, 2018)

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Zooplankton ecology and trophic resources for rearing native fish on an agricultural floodplain in the Yolo Bypass California, USA - Nicholas J. Corline; Ted Sommer; Carson A. Jeffres; Jacob Katz (Wetlands Ecology and Management, 2017)

Foliar bacteria and soil fertility mediate seedling performance: a new and cryptic dimension of niche differentiation - Eric A. Griffin; M. Brian Traw; Peter J. Morin; Jonathan N. Pruitt; S. Joseph Wright; Walter P. Carson (Ecology, 2016)
The phyllosphere (comprising the leaf surface and interior) is one of the world's largest microbial habitats and is host to an abundant and diverse array of bacteria. Nonetheless, the degree to which bacterial communities are benign, harmful, or beneficial to plants in situ is unknown. We tested the hypothesis that the net effect of reducing bacterial abundance and diversity would vary substantially among host species (from harmful to beneficial) and this would be strongly mediated by soil resource availability. To test this, we monitored tree seedling growth responses to commercial antibiotics among replicated resource supply treatments (N, P, K) in a tropical forest in Panama for 29 months. We applied either antibiotics or control water to replicated seedlings of five common tree species ( Alseis blackiana , Desmopsis panamensis , Heisteria concinna , Sorocea affinis , and Tetragastris panamensis ). These antibiotic treatments significantly reduced both the abundance and diversity of bacteria epiphytically as well as endophytically. Overall, the effect of antibiotics on performance was highly host specific. Applying antibiotics increased growth for three species by as much as 49% ( Alseis , Heisteria , and Tetragastris ), decreased growth for a fourth species by nearly 20% ( Sorocea ), and had no impact on a fifth species ( Desmopsis ). Perhaps more importantly, the degree to which foliar bacteria were harmful or not varied with soil resource supply. Specifically, applying antibiotics had no effect when potassium was added but increased growth rate by almost 40% in the absence of potassium. Alternatively, phosphorus enrichment caused the effect of bacteria to switch from being primarily beneficial to harmful or vice versa, but this depended entirely on the presence or absence of nitrogen enrichment (i.e., important and significant interactions). Our results are the first to demonstrate that the net effect of reducing the abundance and diversity of bacteria can have very strong positive and negative effects on seedling performance. Moreover, these effects were clearly mediated by soil resource availability. Though speculative, we suggest that foliar bacteria may interact with soil fertility to comprise an important, yet cryptic dimension of niche differentiation, which can have important implications for species coexistence.

The effects of intranasal oxytocin in opioid-dependent individuals and healthy control subjects: a pilot study - Josh D. Woolley; Peter A. Arcuni; Christopher S. Stauffer; Daniel Fulford; Dean S. Carson; Steve Batki; Sophia Vinogradov (Psychopharmacology, 2016)

Evaluating the ecological impacts of salvage logging: can natural and anthropogenic disturbances promote coexistence? - Alejandro A. Royo; Chris J. Peterson; John S. Stanovick; Walter P. Carson (Ecology, 2016)
Salvage logging following windthrow is common throughout forests worldwide even though the practice is often considered inimical to forest recovery. Because salvaging removes trees, crushes seedlings, and compacts soils, many warn this practice may delay succession, suppress diversity, and alter composition. Here, over 8 yr following windthrow, we experimentally evaluate how salvaging affects tree succession across 11 gaps in Eastern deciduous forests of Pennsylvania, wherein each gap was divided into salvaged and control (unsalvaged) halves. Our gaps vary in size and windthrow severity, and we explicitly account for this variation as well as variation in soil disturbance (i.e., scarification) resulting from salvaging so that our results would be generalizable. Salvage logging had modest and ephemeral impacts on tree succession. Seedling richness and density declined similarly over time in both salvaged and unsalvaged areas as individuals grew into saplings. The primary impact of salvaging on succession occurred where salvaging scarified soils. Here, salvaging caused 41 to 82% declines in sapling abundance, richness, and diversity, but these differences largely disappeared within 5 yr. Additionally, we documented interactions between windthrow severity and scarification. Specifically, low‐severity windthrow and scarification combined reinforced dominance by shade‐tolerant and browse‐tolerant species ( Acer pensylvanicum, Fagus grandifolia ). In contrast, high windthrow severity and scarification together reduced the density of a fast‐growing pioneer tree ( Prunus pensylvanica ) and non‐tree vegetation cover by 75% and 26%, respectively. This reduction enhanced the recruitment of two mid‐successional tree species, Acer rubrum and Prunus serotina , by 2 and 3‐fold, respectively. Thus, our findings demonstrate that salvaging creates novel microsites and mitigates competing vegetation, thereby enhancing establishment of important hardwoods and promoting tree species coexistence. Our results, coupled with an assessment of 27 published post‐windthrow salvage studies, suggest short‐term studies may overestimate the impact of salvaging on regeneration. We conclude that the ecological costs and benefits of salvaging depend upon the variation in canopy and soil disturbance severity as well as the timescale at which effects are evaluated. Thus, our findings are inconsistent with the view that salvaging inexorably undermines plant diversity; rather we suggest salvaging can promote tree species coexistence within various contexts.

Tunable Release of Multiclass Anti-HIV Drugs that are Water-Soluble and Loaded at High Drug Content in Polyester Blended Electrospun Fibers - Daniel Carson; Yonghou Jiang; Kim A. Woodrow (Pharmaceutical Research, 2016)

Coastal sea level changes, observed and projected during the 20th and 21st century - M. Carson; A. Köhl; D. Stammer; A. B. A. Slangen; C. A. Katsman; R. S. W. van de Wal; J. Church; N. White (Climatic Change, 2016)

Development and application of molecular methods ( PCR ) for detection of Tasmanian Atlantic salmon reovirus - S C Zainathan; G Carlile; J Carson; K A McColl; M St. J Crane; L M Williams; J Hoad; N J G Moody; H M Aiken; G F Browning; B F Nowak (Journal of Fish Diseases, 2015)
Molecular ( PCR ) diagnostic tests for the detection and identification of aquareovirus in general, and Tasmanian Atlantic salmon reovirus ( TSRV ) specifically, were developed, and their diagnostic sensitivity and specificity were determined and compared with virus isolation in cell culture. Intralaboratory and interlaboratory comparison of PCR (conventional hemi‐nested RT‐PCR & RT ‐ qPCR ) and virus isolation in cell culture using finfish cell lines, CHSE ‐214 and EPC , was carried out for the detection and identification of TSRV using field samples of farmed Atlantic salmon Salmo salar, L. from various aquaculture sites around Tasmania. The interlaboratory comparison of diagnostic methods was carried out between two laboratories, AAHL ‐ CSIRO and DPIPWE ‐Tasmania. A total of 144 fish from nine sites (12–33 fish per site) were sampled from two regions of Tasmania (Tamar River estuary in the north and Huon River estuary in the south‐east) during late spring to early summer of 2009, and the data were analysed using different statistical approaches. The prevalence of TSRV ranged from 6% to 22% in both regions. All the diagnostic methods (data from both laboratories) had high specificity, while the estimated sensitivity varied between tests with RT ‐ qPCR being the most sensitive (95.2%) method followed by virus isolation and then conventional hemi‐nested RT‐PCR .

Maternal Behavior and Physiological Stress Levels in Wild Chimpanzees (Pan troglodytes schweinfurthii) - Margaret A. Stanton; Matthew R. Heintz; Elizabeth V. Lonsdorf; Rachel M. Santymire; Iddi Lipende; Carson M. Murray (International Journal of Primatology, 2015)

The Ecology and Natural History of Foliar Bacteria with a Focus on Tropical Forests and Agroecosystems - Eric A. Griffin; Walter P. Carson (The Botanical Review, 2015)

Lianas in gaps reduce carbon accumulation in a tropical forest - Stefan A. Schnitzer; Geertje van der Heijden; Joseph Mascaro; Walter P. Carson (Ecology, 2014)
Treefall gaps are the “engines of regeneration” in tropical forests and are loci of high tree recruitment, growth, and carbon accumulation. Gaps, however, are also sites of intense competition between lianas and trees, whereby lianas can dramatically reduce tree carbon uptake and accumulation. Because lianas have relatively low biomass, they may displace far more biomass than they contribute, a hypothesis that has never been tested with the appropriate experiments. We tested this hypothesis with an 8‐yr liana removal experiment in central Panama. After 8 years, mean tree biomass accumulation was 180% greater in liana‐free treefall gaps compared to control gaps. Lianas themselves contributed only 24% of the tree biomass accumulation they displaced. Scaling to the forest level revealed that lianas in gaps reduced net forest woody biomass accumulation by 8.9% to nearly 18%. Consequently, lianas reduce whole‐forest carbon uptake despite their relatively low biomass. This is the first study to demonstrate experimentally that plant–plant competition can result in ecosystem‐wide losses in forest carbon, and it has critical implications for recently observed increases in liana density and biomass on tropical forest carbon dynamics.

Projecting twenty-first century regional sea-level changes - A. B. A. Slangen; M. Carson; C. A. Katsman; R. S. W. van de Wal; A. Köhl; L. L. A. Vermeersen; D. Stammer (Climatic Change, 2014)

Ecosystem classifications based on summer and winter conditions - Margaret E. Andrew; Trisalyn A. Nelson; Michael A. Wulder; George W. Hobart; Nicholas C. Coops; Carson J. Q. Farmer (Environmental Monitoring and Assessment, 2013)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Examination of behavioral strategies regulating cocaine intake in rats - Benjamin A. Zimmer; Carson V. Dobrin; David C. S. Roberts (Psychopharmacology, 2013)

Delivery of Water-Soluble Drugs Using Acoustically Triggered Perfluorocarbon Double Emulsions - Mario L. Fabiilli; James A. Lee; Oliver D. Kripfgans; Paul L. Carson; J. Brian Fowlkes (Pharmaceutical Research, 2010)

Divergence genetics analysis reveals historical population genetic processes leading to contrasting phylogeographic patterns in co‐distributed species - TAMARA M. McGOVERN; CARSON C. KEEVER; CHRISTOPHER A. SASKI; MICHAEL W. HART; PETER B. MARKO (Molecular Ecology, 2010)
Coalescent samplers are computational time machines for inferring the historical demographic genetic processes that have given rise to observable patterns of spatial genetic variation among contemporary populations. We have used traditional characterizations of population structure and coalescent‐based inferences about demographic processes to reconstruct the population histories of two co‐distributed marine species, the frilled dog whelk, Nucella lamellosa , and the bat star, Patiria miniata . Analyses of population structure were consistent with previous work in both species except that additional samples of N. lamellosa showed a larger regional genetic break on Vancouver Island (VI) rather than between the southern Alexander Archipelago as in P. miniata . Our understanding of the causes, rather than just the patterns, of spatial genetic variation was dramatically improved by coalescent analyses that emphasized variation in population divergence times. Overall, gene flow was greater in bat stars (planktonic development) than snails (benthic development) but spatially homogeneous within species. In both species, these large phylogeographic breaks corresponded to relatively ancient divergence times between populations rather than regionally restricted gene flow. Although only N. lamellosa shows a large break on VI, population separation times on VI are congruent between species, suggesting a similar response to late Pleistocene ice sheet expansion. The absence of a phylogeographic break in P. miniata on VI can be attributed to greater gene flow and larger effective population size in this species. Such insights put the relative significance of gene flow into a more comprehensive historical biogeographic context and have important implications for conservation and landscape genetic studies that emphasize the role of contemporary gene flow and connectivity in shaping patterns of population differentiation.

Lianas suppress tree regeneration and diversity in treefall gaps - Stefan A. Schnitzer; Walter P. Carson (Ecology Letters, 2010)
Ecology Letters (2010) 13: 849–857 Abstract Treefall gaps are hypothesized to maintain diversity by creating resource‐rich, heterogeneous habitats necessary for species coexistence. This hypothesis, however, is not supported empirically for shade‐tolerant trees, the dominant plant group in tropical forests. The failure of gaps to maintain shade‐tolerant trees remains puzzling, and the hypothesis implicated to date is dispersal limitation. In central Panama, we tested an alternative ‘biotic interference’ hypothesis: that competition between growth forms (lianas vs. trees) constrains shade‐tolerant tree recruitment, survival and diversity in gaps. We experimentally removed lianas from eight gaps and monitored them for 8 years, while also monitoring nine un‐manipulated control gaps. Removing lianas increased tree growth, recruitment and richness by 55, 46 and 65%, respectively. Lianas were particularly harmful to shade‐tolerant species, but not pioneers. Our findings demonstrate that competition between plant growth forms constrains diversity in a species‐rich tropical forest. Because lianas are abundant in many tropical systems, our findings may apply broadly.

The ‘Expansion-Contraction’ model of Pleistocene biogeography: rocky shores suffer a sea change? - PETER B. MARKO; JESSICA M. HOFFMAN; SANDRA A. EMME; TAMARA M. MCGOVERN; CARSON C. KEEVER; L. NICOLE COX (Molecular Ecology, 2010)

Pervasive interactions between ungulate browsers and disturbance regimes promote temperate forest herbaceous diversity - Alejandro A. Royo; Rachel Collins; Mary Beth Adams; Chad Kirschbaum; Walter P. Carson (Ecology, 2010)
Disruptions to historic disturbance and herbivory regimes have altered plant assemblages in forests worldwide. An emerging consensus suggests that these disruptions often result in impoverished forest biotas. This is particularly true for eastern U.S. deciduous forests where large gaps and understory fires were once relatively common and browsers were far less abundant. Although much research has focused on how disturbance and browsers affect tree diversity, far less attention has been devoted to forest understories where the vast majority (>75%) of the vascular species reside. Here we test the hypothesis that the reintroduction of disturbances resembling historic disturbance regimes and moderate levels of ungulate browsing enhance plant diversity. We explore whether once‐common disturbances and their interaction with the top‐down influence of browsers can create conditions favorable for the maintenance of a rich herbaceous layer in a region recognized as a temperate biodiversity hotspot in West Virginia, USA. We tested this hypothesis via a factorial experiment whereby we manipulated canopy gaps (presence/absence) of a size typically found in old‐growth stands, low‐intensity understory fire (burned/unburned), and deer browsing (fenced/unfenced). We tracked the abundance and diversity of more than 140 herb species for six years. Interactions among our treatments were pervasive. The combination of canopy gaps and understory fire increased herbaceous layer richness, cover, and diversity well beyond either disturbance alone. Furthermore, we documented evidence that deer at moderate levels of abundance promote herbaceous richness and abundance by preferentially browsing fast‐growing pioneer species that thrive following co‐occurring disturbances (i.e., fire and gaps). This finding sharply contrasts with the negative impact browsers have when their populations reach levels well beyond those that occurred for centuries. Although speculative, our results suggest that interactions among fire, canopy gaps, and browsing provided a variable set of habitats and conditions across the landscape that was potentially capable of maintaining much of the plant diversity found in temperate forests.

Variation in RTN3 and PPIL2 Genes Does not Influence Platelet Membrane β-Secretase Activity or Susceptibility to Alzheimer’s Disease in the Northern Irish Population - Robyn Carson; Amy Jayne McKnight; Stephen Todd; Wei Wei Liu; Shirley Heggarty; David Craig; Bernadette McGuinness; G. Brent Irvine; A. Peter Passmore; Janet A. Johnston (NeuroMolecular Medicine, 2009)

Determination of the compositional change (1999–2006) in the pine forests of British Columbia due to mountain pine beetle infestation - Colin Robertson; Carson J. Q. Farmer; Trisalyn A. Nelson; Ian K. Mackenzie; Michael A. Wulder; Joanne C. White (Environmental Monitoring and Assessment, 2009)

Microsatellite markers for species of the genus Dionda (Cyprinidae) from the American southwest - Mark A. Renshaw; Evan W. Carson; Ashley H. Hanna; Caird E. Rexroad; Trevor J. Krabbenhoft; John R. Gold (Conservation Genetics, 2009)

Muscle wasting and interleukin-6-induced atrogin-I expression in the cachectic Apc Min/+ mouse - Kristen A. Baltgalvis; Franklin G. Berger; Maria Marjorette O. Peña; J. Mark Davis; James P. White; James A. Carson (Pflügers Archiv - European Journal of Physiology, 2009)

Common input to different regions of biceps brachii long head - Benjamin K. Barry; Michael A. Pascoe; Stephan Riek; Richard G. Carson; Roger M. Enoka (Experimental Brain Research, 2009)

Genetic Variation in the α7 Nicotinic Acetylcholine Receptor is Associated with Delusional Symptoms in Alzheimer’s Disease - Robyn Carson; David Craig; Dominic Hart; Stephen Todd; Bernadette McGuinness; Janet A. Johnston; Francis A. O’Neill; Craig W. Ritchie; A. Peter Passmore (NeuroMolecular Medicine, 2008)

BACE1 Polymorphisms Do Not Influence Platelet Membrane β-secretase Activity or Genetic Susceptibility for Alzheimer’s Disease in the Northern Irish Population - S. Todd; A. J. McKnight; W. W. Liu; R. Carson; S. Heggarty; B. McGuinness; G. B. Irvine; D. Craig; A. P. Passmore; J. A. Johnston (NeuroMolecular Medicine, 2008)

Ephemeral floodplain habitats provide best growth conditions for juvenile Chinook salmon in a California river - Carson A. Jeffres; Jeff J. Opperman; Peter B. Moyle (Environmental Biology of Fishes, 2008)

Light reduction predicts widespread patterns of dominance between asters and goldenrods - Joshua A. Banta; Scott C. Stark; Martin H. H. Stevens; Thomas H. Pendergast; Anthony Baumert; Walter P. Carson (Plant Ecology, 2008)

Intramuscular aripiprazole for the treatment of acute agitation in patients with schizophrenia or schizoaffective disorder: a double-blind, placebo-controlled comparison with intramuscular haloperidol - Raisa Andrezina; Richard C. Josiassen; Ronald N. Marcus; Dan A. Oren; George Manos; Elyse Stock; William H. Carson; Taro Iwamoto (Psychopharmacology, 2006)

The neurocognitive effects of aripiprazole: an open-label comparison with olanzapine - Robert S. Kern; Michael F. Green; Barbara A. Cornblatt; J. Randall Owen; Robert D. McQuade; William H. Carson; Mirza Ali; Ron Marcus (Psychopharmacology, 2006)

Movement of Sacramento Sucker, Catostomus occidentalis, and Hitch, Lavinia exilicauda, during a Spring Release of Water from Camanche Dam in the Mokelumne River, California - Carson A. Jeffres; A. Peter Klimley; Joseph E. Merz; Joseph J. Cech (Environmental Biology of Fishes, 2006)

Land Use, Spatial Scale, and Stream Systems: Lessons from an Agricultural Region - Bruce Vondracek; Kristen L. Blann; Carson B. Cox; Julia Frost Nerbonne; Karen G. Mumford; Brian A. Nerbonne; Laurie A. Sovell; Julie K. H. Zimmerman (Environmental Management, 2005)

The herb community of a tropical forest in central Panamá: dynamics and impact of mammalian herbivores - Alejandro A. Royo; Walter P. Carson (Oecologia, 2005)

QTL associations for density and diameter in Pinus radiata and the potential for marker-aided selection - M. E. Devey; S. D. Carson; M. F. Nolan; A. C. Matheson; C. Te Riini; J. Hohepa (Theoretical and Applied Genetics, 2004)

Governing coordination: behavioural principles and neural correlates - R. G. Carson; J. A. S. Kelso (Experimental Brain Research, 2004)

RhoA induction by functional overload and nandrolone decanoate administration in rat skeletal muscle - Joseph M. McClung; Won J. Lee; Raymond W. Thompson; Larry L. Lowe; James A. Carson (Pflügers Archiv - European Journal of Physiology, 2003)

Coral‐reef sounds enable nocturnal navigation by some reef‐fish larvae in some places and at some times - J. M. Leis; B. M. Carson‐Ewart; A. C. Hay; D. H. Cato (Journal of Fish Biology, 2003)
At Lizard Island, Great Barrier Reef, catches of fish larvae by light traps that broadcast nocturnal reef sounds (noisy traps) were compared with catches by quiet traps over two 2·5 week new‐moon periods in November (XI) 2000 and January (I) 2001. Three areas were sampled: near‐reef (NR, 500 m from the shore) in I, middle (M, 650 m) in I and XI and offshore (O, >1000 m) in XI. The most abundant taxa captured were Apogonidae, Blenniidae, Chaetodontidae, Lethrinidae, Mullidae and Pomacentridae. Significant differences in catch were found between areas, and a position effect was found at the O and M areas. At the NR and M areas, no taxa had significantly greater catches in quiet traps, but larvae of five taxa had significantly greater catches in noisy traps. These were (areas and times of greater catches): Apogonidae (NR; M XI), Mullidae (M I & XI), Pomacentridae (NR; M I & XI), Serranidae (M I) and Sphyraenidae (NR). At the offshore area, five taxa (Apogonidae, Blenniidae, Chaetodontidae, Mullidae and Pomacentridae) had significantly greater catches in quiet traps and only Lethrinidae had significantly greater catches in noisy traps. Thus some taxa (particularly apogonids and pomacentrids which had catches up to 155% greater in noisy traps, but also lethrinids and mullids, and perhaps others), were attracted to reef sounds at night, but this apparently varied with location and time. The sound‐enhanced catches imply a radius of attraction of the sound 1·02–1·6 times that of the light. More than 65 m from the speaker,the broadcast sound levels at frequencies typical of fish hearing were equivalent to background levels, providing a maximum radius of sound attraction in this experiment.

Temporal and spatial distribution of paramoebae in the water column – a pilot study - G M Douglas‐Helders; D P O'Brien; B E McCorkell; D Zilberg; A Gross; J Carson; B F Nowak (Journal of Fish Diseases, 2003)
Amoebic gill disease is the main disease affecting the salmonid industry in Tasmania, but no information on the distribution of the causative pathogen, Neoparamoeba pemaquidensis , in the aquatic environment is available. This pilot study aimed to determine temporal and spatial distributions of paramoebae species in the water column, using an immuno‐dot blot technique. Water samples were collected from inside fish cages at various depths (0.5, 5.5 and 11.0 m) in both summer and winter, as well as various distances (0, 0.5, 240, 280, 750 and 1100 m) away from the sea cage and farming site. Paramoebae densities were estimated using the most probable number technique (MPN). Temperature, salinity, dissolved oxygen, turbidity, nitrite and nitrates, and bacterial counts were measured for each water sample. Data were analysed using a residual maximum likelihood test and significant associations between paramoebae densities and environmental factors were analysed. Results showed that densities were significantly higher in summer ( P = 0.017), at 5.5 m depth ( P = 0.029), and reduced to the lowest density at 1100 m away from the cage sites ( P = 0.008). Bacterial counts, turbidity and temperature were found to be significantly associated with paramoebae densities.

Herbivore and pathogen damage on grassland and woodland plants: a test of the herbivore uncertainty principle - Stefan A. Schnitzer; Peter B. Reich; Belle Bergner; Walter P. Carson (Ecology Letters, 2002)
Researchers can alter the behaviour and ecology of their study organisms by conducting such seemingly benign activities as non‐destructive measurements and observations. In plant communities, researcher visitation and measurement of plants may increase herbivore damage in some plant species while decreasing it in others. Simply measuring plants could change their competitive ability by altering the amount of herbivore damage that they suffer. Currently, however, there is only limited empirical evidence to support this `herbivore uncertainty principle' (HUP). We tested the HUP by quantifying the amount of herbivore and pathogen damage in 13 plant species (> 1400 individuals) at four different visitation intensities at Cedar Creek Natural History Area, Minnesota, USA. Altogether, we found very little evidence to support the HUP at any intensity of visitation. Researcher visitation did not alter overall plant herbivore damage or survival and we did not detect a significant visitation effect in any of the 13 species. Pathogen damage also did not significantly vary among visitation treatments, although there was some evidence that high visitation caused slightly higher pathogen damage. Based on our results, we question whether this phenomenon should be considered a `principle' of plant ecology.

Differential experimental micrometastasis to lung, liver, and bone with lacZ-tagged CWR22R prostate carcinoma cells - Julianne L. Holleran; Carson J. Miller; Nancy L. Edgehouse; Theresa P. Pretlow; Lloyd A. Culp (Clinical & Experimental Metastasis, 2002)

The water-soluble components of the essential oil of Melaleuca alternifolia (tea tree oil) suppress the production of superoxide by human monocytes, but not neutrophils, activated in vitro - C. Brand; A. Ferrante; R.H. Prager; T.V. Riley; C.F. Carson; J.J. Finlay-Jones; P.H. Hart (Inflammation Research, 2001)

Hepatitis E virus infection in chimpanzees: a retrospective analysis - K. A. McCaustland; K. Krawczynski; J. W. Ebert; M. S. Balayan; A. G. Andjaparidze; J. E. Spelbring; E. H. Cook; C. Humphrey; P. O. Yarbough; M. O. Favorov; D. Carson; D. W. Bradley; et al. (Archives of Virology, 2000)

Activation of the skeletal α-actin promoter during muscle regeneration - Daniel R. Marsh; James A. Carson; Lynn N. Stewart; Frank W. Booth (Journal of Muscle Research and Cell Motility, 1998)

Frequency Control in Synchronized Networks of Inhibitory Neurons - Carson C. Chow; John A. White; Jason Ritt; Nancy Kopell (Journal of Computational Neuroscience, 1998)

Expression and chromosomal localization of the Requiem gene - Theodore G. Gabig; Colin D. Crean; Alison Klenk; Haiyan Long; Neal G. Copeland; Debra J. Gilbert; Nancy A. Jenkins; Danielle Quincey; Fabienne Parente; Françoise Lespinasse; Georges F. Carle; Patrick Gaudray; et al. (Mammalian Genome, 1998)

Myogenin mRNA is elevated during rapid, slow, and maintenance phases of stretch-induced hypertrophy in chicken slow-tonic muscle - James A. Carson; F. W. Booth (Pflügers Archiv - European Journal of Physiology, 1998)

Synchronization and Oscillatory Dynamics in Heterogeneous, Mutually Inhibited Neurons - John A. White; Carson C. Chow; Jason Rit; Cristina Soto-Treviño; Nancy Kopell (Journal of Computational Neuroscience, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Germ-free and barrier-raised TGFβ1-deficient mice have similar inflammatory lesions - Gregory P. Boivin; Iiona Ormsby; Jessica Jones-Carson; Barbara A. O'Toole; Thomas Doetschman (Transgenic Research, 1997)

IgG rheumatoid factors isolated by the surface-displaying phage library technique - Yi-Yuan Yang; Peter Fischer; Sy-Jye C. Leu; Tsaiwei Olee; Dennis A. Carson; P. P. Chen (Immunogenetics, 1997)

Specificity of siderophore-mediated transport of iron in rhizobia - K. C. Carson; A. R. Glenn; M. J. Dilworth (Archives of Microbiology, 1994)

Specificity of siderophore-mediated transport of iron in rhizobia - K. C. Carson; A. R. Glenn; M. J. Dilworth (Archives of Microbiology, 1994)

Siderophore and organic acid production in root nodule bacteria - K. C. Carson; S. Holliday; A. R. Glenn; M. J. Dilworth (Archives of Microbiology, 1992)